(untitled) (Zaporizhzhia Historical Review, 2021)
The problems of ukrainization in the Russian army, particularly in those military units, which were included into Odessa garrison are considered in this article. These processes were initiated by outstanding figures of the Ukrainian ìRuhî (movement) of Odessa, as necessary condition for proclaiming the autonomy of Ukraine. At the same time this demand caused strong resistance from Russian revolutionary government bodies. As a result of fierce political struggle the Ukrainian government bodies of Odessa could a lot of Ukrainian military units.